Usefulness and limitations of taste sensors in the evaluation of palatability and taste-masking in oral dosage forms - Tamami Haraguchi; Miyako Yoshida; Honami Kojima; Takahiro Uchida (Elsevier, 2016)
The purpose of this review is to discuss the advantages and limitations of taste sensors in the evaluation of the taste of palatability of different oral dosage forms. First, we consider some ways in which the palatability of various pharmaceutical formulations including orally disintegrating tablets (ODTs) are tested using two different taste sensors. Second, we focus on the evaluation of palatability of ODTs. We compare the usefulness of three pieces of apparatus for estimating the disintegration time of ODTs. Finally, we compare the characteristics of the two taste sensors in the evaluation of palatability of various kinds of drug formulations.